Probiotics Against Viral Infections: Current Clinical Trials and Future Perspectives - Tello-Reyes, M (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Viral infections represent a major health problem worldwide. Due to the wide variety of etiological agents and their increasing resistance to anti-virals and antibiotics treatments, new strategies for effective therapies need to be developed. Scientific evidence suggests that probiotics may have prophylactic and therapeutic effects in viral diseases. Indeed, these microorganisms interact harmoniously with the intestinal microbiota and protect the integrity of the intestinal barrier as well as modulate the host immune system. Currently, clinical trials with probiotics have been documented in respiratory tract infections, infections caused by human immunodeficiency viruses, herpes, human papillomavirus and hepatic encephalopathy. However, the benefits documented so far are difficult to extrapolate, due to the strain-dependent effect. In addition, the dose of the microorganism used as well as host characteristics are other parameters that should be consider when advocating the use of probiotics to treat viral infections. This review addresses the scientific evidence of the efficacy of probiotics in clinical strains perspective in viral infectious diseases in the last 10 years. © 2021 by the authors.